The place of the visually challenged in mainstream media: The Zimbabwean case - Muromo, B. (Midlands State University, 2015)
Mass media are business entities whose main purpose is profit. Consequently they have been known to pay no or less attention to audiences that do not interest advertisers. In Zimbabwe and a number of other Southern African countries television is the only medium that has attempted to accommodate the physically challenged individuals namely the deaf and dumb by providing sign language translations of news bulletins. This is what is only offered as no other programming like entertainment follows suit. The thrust of this paper is to analyse how the visually challenged access information through the mass media. In Zimbabwe the visually challenged are mostly beggars at street corners hence being denigrated by society and even the media. These are a minority group that fail to catch the attention of media practitioners except on radio. No newspapers are in Braille and television is a luxury mainly for the sighted. Through interviews with the visually challenged themselves and media houses, it was established that no plans are in place to assist the visually handicapped so that they have access to information. It is recommended that what the television is doing for the deaf and dumb should be extended to the visually challenged people in print media.